Investigations to determine the long-term sustainable yield of the Karoo aquifer and the sustained availability of groundwater for small-scale irrigation projects, in Dendera area, Kwekwe District - Zimbabwe - Njanike, Joseph Tendayi (Rhodes University, Faculty of Science, Department of Geology, 2001)
In this thesis the long-term sustainable yield of the Karoo sediment aquifer unit occurring in Dendera area of Kwekwe District is investigated, with the object of providing quantitative data on the sustained availability of groundwater for small-scale irrigation projects. Archaean Basement Schists and Pre-Cambrian gneissic granites, the Basement Complex rocks, underlie the entire study area. Overlying these are Upper Karoo sediments. Aeolian Kalahari sands unconformably mantle higher interfluves, while redistributed sands occur along valleys of major rivers and streams. The Karoo sediments, which predominantly consist of loosely cemented, fine- to medium-grained sandstone alternating with red siltstone and mudstone, constitute the main aquifer. The thickness of the Karoo sediment unit ranges from 30m to 80m. The hydraulic parameters of the Karoo sediment aquifer were characterised in the field by constant discharge pumping tests and slug tests. Pumping tests indicated unconfined conditions and thus the Neuman's method of analysis has been used. Transmissivities from pumping tests are within the range 4.7 mÂ²/d to 13.6 mÂ²/d with an average of 8.9mÂ²/d. The low transmissivities seem to be a major limiting factor in the exploitation of the groundwater resources. Thus the sustainable borehole yields tend to be small, mean values ranging from 33 mÂ²/d to 253 mÂ²/d. Specific yield could not be determined from the pumping tests due to the lack of observation boreholes. Low chemical concentrations render the water suitable for irrigation of all crops, while neither total nor any individual concentrations present health hazards to human or livestock. An average recharge value of 47.7 mm/y was inferred from water table fluctuation method. Chloride mass balance technique in the same area indicates recharge value in the order of 67.4 mm/y. Because the chloride mass balance gives a long-term mean annual recharge, the recharge figure of 67.4 mm/y was adopted for the study area. Based on the abstractable proportion of recharge, the sustainably exploitable volume of groundwater of the order of 2.68 x 10â · mÂ³/y was established. This volume is more than 100 times the estimated current demand for groundwater (1.35 x 10â µ mÂ³/d), implying that there are large volumes of surplus water, which can be utilised for irrigation.
Keywords: Groundwater; Irrigation -- Equipement and supplies; Irrigation -- Kwekwe (Zimbabwe)